Do innovation policies and fintech create synergistic effects for the sustainability of urban green innovation? - Cunlin Li; Shiyu Zhang (Sustainable Futures)
In light of the increasing global emphasis on environmental sustainability, it is essential to comprehend the synergies between innovation policies and financial technologies in promoting sustainable green innovation.This paper examines the synergistic effect of innovation policy and fintech (IPFT) on green innovation sustainability to determine whether creating a technology market enhances this effect. Analyzing data from 284 Chinese cities between 2009 and 2020 using a difference-in-difference-in-difference (DDD) model and various robustness tests, we find substantial evidence that IPFT significantly enhances the sustainability of urban green innovation. Compared to the effects of standalone ''innovation policy'' and ''fintech,'' IPFT has a stronger synergistic impact on urban green innovation sustainability. Research on its influencing mechanisms reveals that IPFT promotes green innovation sustainability in cities by enhancing the level of artificial intelligence and reducing carbon emission intensity. Furthermore, a heterogeneity analysis of urban innovation levels and green development characteristics in different regions indicates that the impact of IPFT on urban green innovation sustainability is mainly observed in cities with low innovation levels and high green development. The findings of this paper offer valuable insights for enhancing green innovation sustainability. They also serve as a reference for other nations and regions, especially developing countries, to promote the sustainable development of urban green innovation.